Baker, Herbert (Sir) and Masey. Parliament Houses additions, cape Town. February 1910. Plan, ink on paper. - Baker, Herbert (Sir) (My University, 2011)
Baker, Herbert (Sir) & Masey. Parliament Houses additions, Cape Town. Plan, ink on paper.
Plan 588x845
Keywords: Baker, Herbert (Sir) & Masey. Parliament Houses additions, Cape Town. Plan, ink on paper.